Hearing and Sound Communication in Amphibians - Narins, Peter M.; Feng, Albert S.; Fay, Richard R. (Springer Handbook of Auditory Research,, 2006)
Hearing and Sound Communication in Amphibians is a compendium of the latest research on acoustic communication in these highly vocal vertebrates. The chapters are written by experts currently investigating the physiology and behavior of amphibians both in the laboratory and in the field. This integrated approach guides each chapter and provides a neuroethologically-driven and evolutionary basis for our understanding of acoustic communication and its underlying mechanisms. The intended audience ranges from senior undergraduates to physiologists, zoologists, evolutionary biologists and communication specialists. Contents Peter Narins is Professor in the Departments of Physiological Science, Ecology & Evolutionary Biology, the Brain Research Institute and the Center for Tropical Research at the University of California, Los Angeles. Albert Feng is Professor in the Departments of Molecular and Integrative Physiology & Bioengineering, Neuroscience Program, Center for Biophysics and Computational Biology, and Beckman Institute at the University of Illinois at Urbana-Champaign. Arthur N. Popper is Professor in the Department of Biology and Co-Director of the Center for Comparative and Evolutionary Biology of Hearing at the University of Maryland, College Park. Richard R. Fay is Director of the Parmly Hearing Institute and Professor of Psychology at Loyola University of Chicago. About the series: The Springer Handbook of Auditory Research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field.